Based on Mendelian Randomization to Explore the Causal Relationship with Insomnia and Gut Microbiota - GUO Yumeng, CUI Yanglin, ZHANG Xianzhong (Zhongguo quanke yixue)
Background As the prevalence of insomnia is gradually increasing, it is seriously affecting the mental and work status of patients. The gut microbiota is considered to be a risk factor for insomnia, but there is a relative lack of evidence to accurately recognize the relationship between gut microbiota and insomnia. Objective Using two-sample Mendelian randomization as a research methodology to explore the causal relationship between gut microbiota and insomnia. Methods Single nucleotide polymorphisms (SNPs) significantly associated with the relative abundance of 196 gut microorganisms were extracted as instrumental variables (IVs) according to predefined thresholds using pooled statistics of the gut microbiota from the largest available genome-wide meta-analysis of association studies conducted by the MiBioGen consortium (n=18 340). Pooled statistics for insomnia were obtained from the UK Biobank (n=462 341). Inverse variance weighting (IVW), MR-Egger regression, weighted median (WME), and weighted multinomial (WM) were used to detect the causal relationship between gut microbiota and insomnia, with IVW being the predominant method, and the results were assessed according to the effect indicator dominance ratio (OR) and 95% confidence interval (CI). Sensitivity analysis, heterogeneity test, gene multiplicity test, MR multiplicity residual and outlier test (MR-PRESSO) were combined to verify the stability and reliability of the results. Reverse Mendelian randomization analysis was also performed on the colonies found to be causally associated with insomnia. Results IVW results showed that genus_Roseburia (OR=0.787, 95%CI=0.671-0.923, PFDR=0.016), genus_Erysipelatoclostridium (OR=0.880, 95%CI=0.794-0.976, PFDR=0.077), genus_Paraprevotella (OR=0.891, 95%CI=0.801-0.991, PFDR=0.083), genus_Ruminococcaceae UCG014 (OR=0.818, 95%CI=0.697-0.961, PFDR=0.072), family_Pasteurellaceae (OR=0.897, 95%CI=0.814-0.988, PFDR=0.081), order_Pasteurellales (OR=0.897, 95%CI=0.814-0.988, PFDR=0.094) were associated with insomnia, and no genetic pleiotropy or significant heterogeneity of IVs was found. According to the results of reverse MR analysis, insomnia had no significant causal effect on gut microbiota. Conclusion The abundance of six species of GM from the genus_Roseburia, genus_Erysipelatoclostridium, genus_Paraprevotella, genus_Ruminococcaceae UCG014 group, family_Pasteurellaceae, and order_Pasteurellales is negatively correlated with the risk of developing insomnia, i.e., decreased abundance increased the risk of developing insomnia and is a protective factor against insomnia.